The Role of Mahmudhoja Behbudi in the Educational Reforms of the Jadid Movement - Ismailova , Tozagul (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2025)
The early 20th century marked a period of significant educational reform in Central Asia, a transformation largely shaped by the influential Jadid movement. At the forefront of this reform was Mahmudhoja Behbudi, a pivotal figure whose efforts laid the groundwork for modern education in the region. Behbudi championed the promotion of progressive educational ideas aimed at fostering a new generation of educated individuals who could contribute meaningfully to society. His work included establishing schools that implemented contemporary curricula, emphasizing not only traditional subjects but also modern sciences and languages, thereby broadening the intellectual horizons of his students. Furthermore, his extensive involvement in publishing and printing activities greatly facilitated the dissemination of reformist ideas. As noted, his publishing and printing activities, the development of education reflected in his articles, the training of advanced national personnel underscore the significant impact of Behbudis initiatives on advancing educational reform among the Jadids and beyond (Usmonaliyeva et al., 2023). The connections established with reformers in the Ottoman Empire further influenced Behbudis educational philosophy, reflecting a broader context in which his ideas flourished.